Angkak (red mold rice) as an antihypercholesterolemic and antihypertensive effect: A review - Primanita Setyowati; Elok Zubaidah; Aji Sutrisno (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Red Mold Rice (RMR) or angkak is a fermented product of cooked rice by Monascus mold. RMR mainly contains pigments, monacolins (Monacolin K), andγ-aminobutyric acid (GABA). Monacolin K (MK) is also popular as lovastatin (natural statin). MK are inhibitors of enzyme 3 hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, the main enzim for regulating cholesterol synthesis and exertingpotent serum cholesterol demoting effect. GABA is a prominent inhibitory neurotransmitter found in the central nervous system.Itfunctions as an antihypertensive, anti-inflammation, and antioxidant. This paper provides a review of factors influencing the Monascus fermentation process on the synthesis of the pigments, MK, and GABA, which can relieve hypercholesterolemia and hypertension. The information reviewed for this paper was obtained from the SciFinder, Elsevier, NCBI, Science Direct, Google Scholar, Frontier, MDPI, and M.Sc. and Ph. D dissertations published in August 2021. Maximizing RMR bioactiveyield obtained by optimizing the selection of optimal monascus strain, substrates, and fermentation factor (pH, inoculum dimension, temperature, fermentation time). Comparison between collaboration RMR bioactive activities (MK, GABA) and statin activities arealso examined. Other bioactiveof RMR and their health benefits have been discussed. However, little information about the relationship between RMR bioactive and their effects on reducing hypercholesterolemia and hypertension is available. Red Mold Rice (RMR) or angkak is a fermented product of cooked rice by Monascus mold. RMR mainly contains pigments, monacolins (Monacolin K), andγ-aminobutyric acid (GABA). Monacolin K (MK) is also popular as lovastatin (natural statin). MK are inhibitors of enzyme 3 hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, the main enzim for regulating cholesterol synthesis and exertingpotent serum cholesterol demoting effect. GABA is a prominent inhibitory neurotransmitter found in the central nervous system.Itfunctions as an antihypertensive, anti-inflammation, and antioxidant. This paper provides a review of factors influencing the Monascus fermentation process on the synthesis of the pigments, MK, and GABA, which can relieve hypercholesterolemia and hypertension. The information reviewed for this paper was obtained from the SciFinder, Elsevier, NCBI, Science Direct, Google Scholar, Frontier, MDPI, and M.Sc. and Ph. D dissertations published in August 2021. Maximizing RMR bioactiveyield obtained by optimizing the selection of optimal monascus strain, substrates, and fermentation factor (pH, inoculum dimension, temperature, fermentation time). Comparison between collaboration RMR bioactive activities (MK, GABA) and statin activities arealso examined. Other bioactiveof RMR and their health benefits have been discussed. However, little information about the relationship between RMR bioactive and their effects on reducing hypercholesterolemia and hypertension is available.